Cover Feature: Guided Lithium Deposition by Surface Micro‐Patterning of Lithium‐Metal Electrodes (ChemElectroChem 21/2018). Issue 21 (2nd October 2018) - Kim, Yun‐Jung; Jin, Hyun S.; Lee, Dong‐Hyun; Choi, Jaeho; Jo, Wonhee; Noh, Hyungjun; Lee, Jinhong; Chu, Hyunwon; Kwack, Hobeom; Ye, Fangmin; Lee, Hongkyung; Ryou, Myung‐Hyun; et al.
Abstract : The Cover Feature illustrates two different types of micro‐patterned Li‐metal electrodes. The large‐sized patterns accommodate a deposited Li metal inside the holes, so the dendritic growth of Li metal can be effectively suppressed. However, the Li metal electrode with small‐sized patterns at the surface cannot play a critical role in stabilizing the Li‐metal electrode. More information can be found in the Article by Y.‐J. Kim et al onpage 3169 in Issue 21, 2018 (DOI:10.1002/celc.201800694 ).